First Description of the Clinical Activity of Avapritinib in Sporadic Mesenteric Desmoid Tumor - Rebecca Ganzon; Wei Chen; Gabriel Tinoco (Case Reports in Oncological Medicine)
Desmoid tumors (DTs) are rare and locally aggressive with a high rate of local recurrence even with optimal surgical resection. Systemic treatments are often utilized for desmoid cases with high risk of surgical morbidity or for local and symptomatic control of recurrent disease. However, the systemic treatment options for DTs are limited with limited responses. Avapritinib is a tyrosine kinase inhibitor (TKI) approved in 2020 for adults with unresectable or metastatic gastrointestinal (GI) stromal tumors (GISTs) harboring a platelet-derived growth factor receptor alpha (PDGFRA) Exon 18 mutation, including D842V mutations. In this case report, we describe a 55-year-old man with a history of D842V-mutant gastric GIST who presented several years after complete resection of the GIST with an enlarging soft tissue mass in the small intestine. After a nondiagnostic biopsy, the patient was started on avapritinib due to concerns for recurrent D842V-mutant GIST. The tumor had a partial response to treatment by RECIST 1.1 criteria, and the patient underwent surgical resection. The final pathology report revealed a sporadic DT. To our knowledge, this is the first known description of the activity of avapritinib in the treatment of a sporadic mesenteric DT, which is relevant given the limited treatment options for patients with this diagnosis. This clinical finding may be worth exploring in a dedicated clinical trial.